Work Performance and Life Balance Among Female Dormitory Workers in the Digital Era: A Case Study from the Manufacturing Sector - Rusdhiyansyah, Rusdhiyansyah; Azhar Solihin, Shofwan (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study examines the impact of digitalization on the performance and work-life balance of female workers residing in company dormitories, with a focus on PT Indo-Rama Synthetics Tbk, Spun Yarns Division. In the digital era, while workers in manufacturing environments benefit from increased technological access, those living in dormitories face unique challenges. This research adopts a qualitative approach, involving 20 female dormitory residents and 10 non-dormitory workers for comparison. Data were collected through in-depth interviews, observations, and document analysis, and analyzed thematically. The findings show that dormitory workers have better access to digital tools and technology, but their performance is constrained by limited opportunities for training and reduced social interaction. To provide a clearer comparison, the study also applied a simple mean score framework to quantify key perceptions across aspects such as access to technology, training, work-life balance, and psychological well-being. The results revealed consistent gaps between dormitory and non-dormitory workers, particularly in flexibility and social connectivity. The study concludes with recommendations for companies to implement continuous digital training programs, flexible work policies, and enhanced social facilities in dormitories. Further research is encouraged to explore inclusive digitalization strategies and comparative studies between dormitory and non-dormitory workers in different sectors. Keywords: digitalization, performance, work-life balance, female workers, dormitories